Clinical and radiological presentation in patients with conserved blunt liver and splenic injuries at a tertiary care center in western India - Meshram, Prashant (International Surgery Journal, 2019)
Background: There has been an increase in abdominal injuries following industrialisation and urbanisation. The mortality due to these injuries however has shown a declining trend worldwide. This is most probably due to early presentation, better access to health care and improved monitoring and treatment modalities. Methods: 51 patients of conserved blunt liver and/or splenic injuries admitted in the trauma ICU of a tertiary care center were studied over a year for demographics, mode of injuries, pre- hospital delay, clinical and radiological presentation. Results: Majority of the patients were males in the age group of 16-30 years. Vehicular accidents were the commonest mode of injuries. Liver was commonly injured. Both liver and spleen were injured in only 3 patients. 20 out of the injured 51 patients received blood transfusion and majority of them had high grade injuries. The severity of injuries was graded with both USG abdomen and CT scan of the abdomen. There was not much difference in grading of liver and splenic injuries by Ultrasound and CT scan. Conclusions: Blunt liver and splenic injuries were commonly seen in young males. Blood transfusion was required in patients with high grade injuries. USG abdomen can be safely used to grade injuries without much discrepancy when compared to CT abdomen.